Document of Art Exchange Programme : the 1st Fukuoka Asian art Triennale 1999. - Fukuoka Asian Art Museum, Fukuoka; Akiko, Hirayama; Alesworth, David; Aquilizan, Alfredo J.D.; Gupta, Subodh; Heng, Amanda; Kazi, Durriya; Lin, Michael; Masahiro, Ushiroshoji; Shigeaki, Iwai; Takako, Kinoshita; Tsuyoshi, Ozawa; et al. (Fukuoka : Fukuoka Asian Art Museum, 2000)
Murti, Krisna ; Lin, Michael ; Xu Bing ; Kazi, Durriya ; Alesworth, David ; Gupta, Subodh ; Shigeaki, Iwai ; Tsuyoshi, Ozawa ; Nguyen Minh Thanh ; Aquilizan, Alfredo Juan ; Prom Sam An ; Karmakar, Ashoke ; ium ; Matzain, Mahaddi B. Hj. ; Khanthavilay, Douangdy ; Po Po ; Heng, Amanda ; Uma Shankar Shah ; Usehbayar, Zagdin ; Ritsuko, Taho ; Toemsombat, Montri ; Thenuwara, Chandraguptha ; Noor Azizan Rahman Paiman ; Chen Shunchu
2 volumes : V.1: Document of art exchange programme & V.2: Seminar : Asian art - towards the 21st century in kartonnen wikkel
Engels
Japans
1st Fukuoka Asian Art Triennale 1999, FAAM (Fukuoka Asian Art Museum) Fukuoka, 06.03.1999 - 06.06.1999
boek